Efektivitas Program Makan Bergizi Gratis (MBG) dalam Mendukung Pencapaian SDGs 2 dan SDGs 4 di Indonesia - Sheila Rizky Febrianti; Frestya Nova Arianti; Firre An Suprapto (Jurnal Administrasi Publik dan Kebijaka (JAPK), 2026)
Sustainable development identifies adequate nutrition and improved educational quality as two key prerequisites for strengthening human resources. In Indonesia, issues such as stunting, malnutrition, and unequal access to educational services remain challenges that require targeted policy interventions. This study aims to analyze the effectiveness of the Free Nutritious Meals Program (MBG) in supporting the achievement of SDG 2 (Zero Hunger) and SDG 4 (Quality Education). The study employs a descriptive qualitative approach through a literature review using secondary data from government reports, scientific articles, and publications by international organizations. The findings indicate that the MBG has strong potential to expand students’ access to nutritious food, improve daily dietary adequacy, and support long-term stunting prevention. The program also contributes to enhancing students’ learning readiness, concentration, participation, and school attendance. However, the effectiveness of the MBG is highly dependent on the accuracy of targeting, the quality of distribution, food quality standards, consistency of implementation, and equity across regions. Thus, the MBG is relevant as a cross-sectoral policy instrument in supporting SDG 2 and SDG 4, but its impact will only be optimal if its governance and oversight are strengthened.